Shakedown Behavior of a Continuous Steel Bridge Girder Strengthened With Post-Installed Shear Connectors. (November 2016) - Kreitman, Kerry; Ghiami Azad, Amir Reza; Engelhardt, Michael; Helwig, Todd; Williamson, Eric
Abstract: An economical method for strengthening non-composite steel girder bridges is to create composite action by "post-installing" shear connectors to engage the steel girder and concrete deck to act as a unit. Concepts of inelastic moment redistribution can be used to further increase the load-carrying capacity of continuous bridges. This paper presents results from experimental testing of a large-scale girder specimen with post-installed shear connectors under large repeated loads leading to moment redistribution at the shakedown limit state.